Pengetahuan Masyarakat Tentang Taman Obat Keluarga Di Nglinggi, Klaten Selatan - Susilo Yulianto (Jurnal Kebidanan dan Kesehatan Tradisional, 2016)
Abstract: The Knowledge, People, TOGA. Family Medical Plants (TOGA) is one of many traditional medication that usedfor a long time in Indonesia. The successful of this family medical plants programvery depends with people’s knowledge about every single plants that can used asherbal medicine, especially the one with empirical evidence. Beside of that, alsodepends with how people use that herbal medicine for each different case.This research is intended to disclose the description of people’s knowledge andbehaviour about family medical plants at Nglinggi, Klaten Selatan. The present research deploy descriptive method, with 30 respondents assample that selected with simple random sampling. Data collection is conductedtrough guiding interview with respondent and direct observation. Instrument thatused is questionnaire and camera for observation. The data shows that all of respondents agree using herbal medicine foralternative medication, but there are respondents whose not used herbal medicinefor daily medication.The conclusions drawm from this research is people’s knowledge in Klaten is still undertarget, because of that we have to give these people more information abaout family medical plants (TOGA).